On the augmented Zagreb index - Ali, Akbar; Raza, Zahid; Bhatti, Akhlaq Ahmad (Kuwait Journal of Science, 2016)
Topological indices play an important role in Mathematical Chemistry, especially in thequantitative structure-property relationship (QSPR) and quantitative structure-activityrelationship (QSAR) studies. Recent research indicates that to predict the certainphysico-chemical properties of particular types of molecules, the augmented Zagrebindex (AZI) possess the best correlating ability among several topological indices. Themain purpose of the current study is to establish some mathematical properties of thisindex or, more precisely, to report tight bounds for the AZI of chemical bicyclic andchemical unicyclic graphs. A Nordhaus-Gaddum-type result for AZI (of connectedgraph whose complement is connected) is also derived.